Pro PHP : patterns, frameworks, testing and more - McArthur, Kevin (Berkeley, CA : Apress, 2008)
Offers coverage of PHP's advanced object-oriented features and their application to patterns and pattern-driven development, discussing software development patterns, the Standard PHP Library, and MVC software architecture and PHP applications.
Includes index.
Keywords: PHP (Computer program language); PHP (Computer language)